Valproic Acid-Induced Hyperammonemic Encephalopathy as a Cause of Neurologic Deterioration after Unruptured Aneurysm Surgery - Lee, Sangkook; Cheong, Jinhwan; Kim, Choonghyun; Kim, Jae Min (Journal of Korean Neurosurgical Society, 2015)
Neurological deficits after brain surgery are not uncommon, and correct and prompt differential diagnosis is essential to initiate appropriate treatment. We describe a patient suffering from loss of consciousness due to hyperammonemia, following valproic acid treatment after surgery for an unruptured cerebral aneurysm. A 57-year-old female patient underwent successful aneurysmal neck clipping to correct an unruptured aneurysm. Her postoperative course was good, and she received anti-epileptic therapy (valproic acid) and a soft diet. Within a few days the patient experienced mental deterioration. Her serum valproic acid reached toxic levels (149.40 mg/L), and serum ammonia was fifteen times the upper normal limit (553 mmol/L; normal range, 9-33 mmol/L). After discontinuation of valproic acid and with conservative treatment, the patient recovered without any complications. Valproate-induced hyperammonemic encephalopathy is an unusual but serious neurosurgical complication, and should not be disregarded as a possible cause of neurological deficits after neurovascular surgery. Early diagnosis is crucial, as discontinuation of valproic acid therapy can prevent serious complications, including death.